Tytuły w dawnej prasie popularnonaukowej (na przykładzie „Nowych Wiadomości Ekonomicznych i Uczonych” 1758–1761) - Szczaus, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article analyses the structure and functions of seventy-three titles extracted from the first Polish-language popular-science journal, i.e. Nowe Wiadomości Ekonomiczne i Uczone. It was determined that the examined titles included both uninomial and binomial titles (25) as well as multinomial ones (48). Uninomial titles relate only to relatively short texts whose publication fell within a single issue of the journal. Long texts, divided into several parts and published in subsequent issues of the journal, had multinomial titles. The analysed titles (just as in the case of the titles of strictly-scientific modern articles) fulfilled the informative and substantial function. However, they did not perform the pragmatic and persuasive functions typical of the headlines present in modern popular-science press.